Incidence, Risk Factors, and Outcomes of Neonatal Acute Kidney Injury: Protocol of a Multicentric Prospective Cohort Study [The Indian Iconic Neonatal Kidney Educational Registry] - Agrawal, Gopal; Wazir, Sanjay; Sethi, Sidharth Kumar; Tibrewal, Abhishek; Dhir, Rohan; Bajaj, Naveen; Gupta, Naveen Parkash; Mirgunde, Shishir; Sahoo, Jagdish; Balachandran, Binesh; Afzal, Kamran; Shrivastava, Anubha; et al. (Frontiers in Pediatrics, 2021)
BACKGROUND: Acute kidney injury (AKI) is a significant problem in neonates, but the evidence is sparse. Neonatal AKI is an independent risk factor for increased mortality and prolonged hospital stay. There are stark differences in the epidemiology of AKI in neonates amongst the developing and the developed world. Increased prevalence of neonatal sepsis, lack of awareness about neonatal AKI and poor access to pediatric nephrologists add to the improper management of neonatal AKI in the developing countries. METHODS: This study is a multicentric, national, prospective cohort study [The Indian iconic Neonatal Kidney Educational Registry (TINKER)] conducted in level 2-3 NICUs in 11 centers across India. We have enrolled nearly 2000 neonates over the study period. Neonates ( 28 days) who were admitted in NICU and those who received intravenous (IV) fluids for at least 48 hours for hydration and/or nutrition have been included. Data collection included: (1) baseline demographics (2) daily physiologic and laboratory parameters (3) discharge data. KDIGO workgroup AKI definition modified for neonates was used for defining AKI. Data entry was carried out by individual participating centers using a web-based database (akiregistry.org). De-identified data has been maintained and handled by the principal investigator (PI). This collaboration plans to disseminate data through peer-reviewed publications and through presentations at educational conferences. CONCLUSIONS: The purpose of this study is to create the first prospective neonatal all-cause AKI data repository and describe the incidence of neonatal AKI in NICUs in the country and determine the risk factors as well as the outcomes of such neonates – both short-term and long-term outcomes. This will eventually spur therapeutic advancements, facilitate decipherment of epidemiological trends, risk factors as well as outcomes and identify disparities in management across the nation.